3D- flow of a Electrically Conducting and Dissipating Maxwell fluid treated with Ohmic Heating Convective boundary condition: Numerical Analysis - Malliswari, B.; Sreenivasulu, P.; Poornima, T.; Bhaskar Reddy, N. (International Journal of Engineering and Technology, 2018)
An analysis is made to study the effects of radiation, dissipation, Thermo-diffuso and Diffuso- thermo on MHD 3D Maxwell flow past a stretching permeable sheet with resistive heating. Transforming the governing dimensional boundary layer equations using three dimensional similarity transformations and then the resultant equations are numerically solved by employing Shooting method.Â  The effect of the pertinent parameters on various flow distributions is elaborately discussed with the help of graphs and tables. The comparison of present results with the existing literature gave an excellent agreement for the reduced cases.Â Â